PENGARUH PERILAKU ASERTIF KEPALA SEKOLAH TERHADAP MOTIVASI KERJA GURU DI SMA/SEDERAJAT SE-KECAMATAN GONDANGWETAN - Amalia, Robbiatul; Munir, Miftakhul; Halimah, Siti (STKIP Pesisir Selatan, 2025)
The principal's assertive behavior is an important factor that has the potential to influence teacher work motivation, through the ability to communicate openly, provide constructive appreciation, make decisions wisely, and deal with differences of opinion without conflict. Teacher work motivation is a crucial factor in creating effective and quality learning. However, low teacher motivation is still found in some schools, indicated by a lack of enthusiasm in teaching and participation in professional activities. This study aims to examine the assertive behavior of school principals, the level of teacher work motivation, and the influence of principals' assertive behavior on teacher motivation in high schools or equivalent in Gondangwetan sub-district. This research employs an associative quantitative approach using a survey method, involving 65 teachers selected from 188 teachers across 10 schools through purposive sampling. The analysis results show that the assertive behavior of school principals has a positive and significant effect on teacher work motivation (regression coefficient = 0.845; contribution 69%). These findings emphasize that leadership characterized by open communication and professional appreciation of teachers can significantly enhance teacher work motivation.